Complexity of nursing care in acute care hospital patients: results of a pilot study with a newly developed questionnaire. Issue 3 (23rd September 2014) - Kleinknecht‐Dolf, Michael; Grand, Francis; Spichiger, Elisabeth; Müller, Marianne; Martin, Jacqueline S.; Spirig, Rebecca
<x xml:space="preserve">Abstract</x> Aim The aim of this pilot study was to develop an instrument for measuring complexity of nursing care in hospitalised acute care patients as well as to examine its comprehensibility, its feasibility, the effort required for data collection, and its inter‐rater reliability as well as its face validity. Methods This pilot study was designed as a descriptive, explorative cross‐sectional survey with multiple measurements of the patient‐related complexity of nursing care and a supplemental qualitative questionnaire conducted on six units of a Swiss university hospital. The instrument to assess complexity of nursing care was developed on the framework of Perrow and encompasses on three subscales a total of 15 items with a 5‐point Likert scale. Ethical considerations The study was reviewed and approved by the Cantonal Ethics Committee. Results In total, 866 assessments of complexity of nursing care were carried out on 234 patients. The variability of the results of the six units, from three different specialties, suggests that the sampling was suitable for capturing a wide spectrum of complexity. The results of the three subscales are consistent and the discussion of them with the participating units shows that they are also plausible. The verification of the inter‐rater reliability has satisfactory to high intersubjective correlation of the values. There were also a few suggestions for improving comprehensibility as well as on how to support user application. The time expenditure for the assessment between 2 to 5 minutes per patient was accurately. Conclusion With the newly developed questionnaire to measure the complexity of nursing care in acute care hospitals it seems to be possible to assess and to quantify the complexity of nursing care in various acute care hospital settings. Based on the findings and the feedback of the participating users, the questionnaire needs to be improved for large‐scale application.